UNDERSTANDING RESISTANCE AND OHM'S LAW WITH ARDUINO-BASED EXPERIMENTS. - SALAR, R. (Revista Cubana de Física, 2021)
The rapid development of technology has enabled many types of technology to be used frequently by educators in learning and teaching activities. One of these frequently used educational technologies is Arduino. This study aims to determine how resistance changes depending on the cross-sectional area, length, and resistivity of the conductor using Arduino. In order to determine the factors affecting the resistance in the Arduino-based experiment, the experiment utilized the graphite leads that students use in their daily lives. An inexpensive and high mobility experiment system has been developed. The data obtained by the experimental setup complies with theoretical laws. This experiment, along with the use of Arduino, will enable students to experience Ohm's law and enable them to better understand the concepts of potential, current, and resistance in a series circuit. In addition, it is thought that the experiment will attract more attention from students by offering a technology-supported learning opportunity. Researchers and teachers can turn this experiment into a science, technology, engineering y mathematics (STEM) activity by integrating it into a problematic situation.